Analysis and improvement of the pad wear profile in fixed abrasive polishing. Issue 5 (July 2016) - Nguyen, N.; Zhong, Z.; Tian, Y.
Abstract Fixed abrasive polishing has some advantages in generating good planarization surfaces with low defects. The surfaces after polishing have better uniformity, and the material removal rate is much higher than that of the traditional chemical mechanical polishing using loose abrasives. One of the most important factors that have significant effects on the uniformity of the polished surface is the pad wear profile. The pad wear profile after a long time of polishing is almost concave, and it has been challenging to create a flat surface. Therefore, there is a requirement for creating a better pad wear profile to improve quality of machined surfaces in chemical-mechanical polishing processes. In this paper, kinematic aspects of the effects of operation parameters on the pad wear profile are investigated, combining with conditioner sizes, pattern, and positions. Based on that, a new model, including new designs of the conditioner and pad, is proposed. This new model has created a convex pad wear profile instead of a concave one. According to the result of the new model, the pad shape after the conditioning process is more uniform than the old one conditioned by the old model. The result was validated by an algorithm which was validated by the experiments reported in our previous paper.